Crop Wild Relatives of Sorghum: A Novel Source of Genetic Variation for Crop Improvement - Vetriventhan, Mani; Jagadeesh, Kommineni; Baraskar, S.; Dagunapur, Naresh Reddy; Srinivas, Raja; Kanchanapally, Anilkumar; Singh, Kuldeep (Springer, 2024)
Sorghum is one of the most important dryland crops with greater prominence in terms of food and fodder, contribution to global food security and nutrition. Sorghum production is constrained by several biotic and abiotic stresses; on the other hand, the repeated use of identical sources in breeding program has resulted in narrow genetic base of crop cultivars. This enhanced the need to broaden the genetic base of crop cultivars by using diverse landraces and crop wild relatives. Currently, 259,595 accessions of sorghum spp. including 2465 wild and weedy relatives are being conserved ex situ in the genebanks across the globe. The exploitation of wild species harboring several desirable alleles for various biotic and abiotic stress tolerance, productivity, and nutritional traits can aid in diversifying the trait sources. Gap analysis of the sorghum wild relatives indicated significant taxonomical and geographical gaps in the global collection, requiring immediate efforts to enrich the gene pool. Using novel breeding strategies including the application of genomics approaches like genome sequencing, trait mapping and pangenome development provides more comprehensive insights into trait-specific sources. This can aid in identifying and transferring novel traits from wild relatives and can lead to sustainable production levels in sorghum.